Assessing individual differences: novelty and ultrasonic vocalizations predict acute and chronic D-amphetamine response in rats - Garcia, Erik J. (Kansas State University, 2014)
Novelty-seeking and sensation-seeking are traits implicated in initial drug experimentation and relapse in human populations. To research the neurobiological substrates that are implicated in novelty/sensation-seeking that predispose an individual to drug use, a rodent model was used. Recently, 50 kHz ultrasonic vocalizations (USV) have been identified as indices of affective state and are evoked by several drugs of abuse, specifically when these drugs of abuse have their pharmacological effects in the mesolimbic dopamine path. Secondly, genetic breeding of high and low vocalizers suggests not only are they different in the calling frequency, but also to drug sensitivity, suggesting ultrasonic vocalizations may be a behavioral marker for individual differences in the mesolimbic dopamine circuit. Two sensation/novelty seeking screens and an ultrasonic vocalization screen were used in rats to predict the locomotor and 50 kHz USV response to a low (.3 mg/kg) and high dose (1.0 mg/kg) of amphetamine. Correlation analysis revealed none of the novelty screens were correlated. Simultaneous regression analyses indicated amphetamine dose-dependently increased locomotor activity acutely and chronically but did not increase 50 kHz USV. The USV assessment predicted USV response to amphetamine acutely and chronically but was not dose dependent. No interactions among any predictors were observed. Previous research has dichotomized the novelty/sensation-seeking trait and found significant differences between high and low novelty responders. The current research provides evidence for maintaining continuous individual difference variables, and suggests each screen measures a different trait implicated in addiction.
Keywords: ultrasonic vocalizations; amphetamine; animal behavior; individual differences; addiction; Psychobiology (0349)